EVALUATION OF THE WATER AGE IN THE WESTERN PART OF JOHOR STRAIT, MALAYSIA (Malaysian Journal of Civil Engineering, 2018)
The age of water is useful for understanding the fundamental mechanisms controlling the flux of substances through an estuary. Furthermore, this variable is useful indicators of the susceptibility of estuaries to eutrophication. In this paper, an application of a three-dimensional hydrodynamic model used to evaluate water age distributions for a range of inflow conditions in the Western Part of Strait of Johor, Malaysia. As a first step, the three dimensional hydrodynamic model EFDC was calibrated and then used to evaluate the spatial distribution of water age. Numerical simulations were completed under different inflow conditions. The analysis suggested considerable spatial variation in the water age under both low and high-flow conditions. The average water age in entire system is maximum 14 days under minimum inflow, 194.4 m 3 /s and minimum 4 days under maximum inflow, 541.3 m3 /s. This analysis helped in recognition of areas of the estuary most vulnerable to oxygen depletion and eutrophication.